2002
DOI: 10.1136/bmj.325.7361.411
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation to airborne moulds and severity of asthma: cross sectional study from European Community respiratory health survey

Abstract: Objective To assess whether the severity of asthma is associated with sensitisation to airborne moulds rather than to other seasonal or perennial allergens. Design Multicentre epidemiological survey in 30 centres. Setting European Community respiratory health survey. Participants 1132 adults aged 20-44 years with current asthma and with skin prick test results. Main outcome measure Severity of asthma according to score based on forced expiratory volume in one second, number of asthma attacks, hospital admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
248
6
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 419 publications
(282 citation statements)
references
References 29 publications
9
248
6
19
Order By: Relevance
“…6 At the Portland, OR, site in the European Community respiratory health survey (ECRHS) studies, 74% of the 39 participants with asthma were sensitized to at least one of 9 common allergens, the most frequent sensitizations being to timothy grass, D. pteronyssinus, birch, A. alternata, and cat. 5 Thus, studies in the United States have consistently observed a high prevalence of atopy among adult asthmatics, with the distribution of specific allergen sensitivities varying between sites. The same observations were reported in the ECRHS studies conducted at 30 sites, mostly in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 At the Portland, OR, site in the European Community respiratory health survey (ECRHS) studies, 74% of the 39 participants with asthma were sensitized to at least one of 9 common allergens, the most frequent sensitizations being to timothy grass, D. pteronyssinus, birch, A. alternata, and cat. 5 Thus, studies in the United States have consistently observed a high prevalence of atopy among adult asthmatics, with the distribution of specific allergen sensitivities varying between sites. The same observations were reported in the ECRHS studies conducted at 30 sites, mostly in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations that have been reported were at single sites and tended to have small sample sizes. 5,6,9 In a study of patients being evaluated by radioallergosorbent testing in New York City, asthmatics were more likely than non-asthmatics to be hypersensitized to cat dander or dust mites (D. farinae) and to Deuteromycetes molds (Alternaria tenuis, Aspergillus fumigatus, and Cladosporium herbarum), whereas pollen (tree, grass, ragweed) hypersensitivity was not independently associated with asthma. 9 Although cat dander was excluded from another New York City study of allergic sensitization, 6 most (83%) of the 29 adults with asthma had a positive skin prick test to at least one of 7 common allergens or allergen mixtures: ragweed, grasses, dust mite (Dermatophagoides pteronyssinus and D. farinae), and trees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations